2020
DOI: 10.24251/hicss.2020.447
|View full text |Cite
|
Sign up to set email alerts
|

Constituting Factors of a Digitally Influenced Relationship between Patients and Primary Care Physicians in Rural Areas

Abstract: In times of an ageing society and a rural exodus of primary care physicians, healthcare systems are facing major challenges. To maintain comprehensive care and an equitable access to healthcare services, today's technological advancements represent a promising measure. Technologies empower patients by providing innovative tools such as sensors and applications for self-measurement, leading to selfinitiated interventions, while supporting physicians in handling rising demands through telemedicine and spatially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…A smaller number of GPs will have to take care of a larger number of patients because of demographic changes and an aging population, and catchment areas will increase [ 4 ]. Furthermore, GPs—especially in rural areas—have problems finding successors for their practices [ 5 , 6 ]. As a result, imbalances, disparities, and inequitable distributions of care occur, which threaten the comprehensive provision of care and the maintenance of population-wide health [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A smaller number of GPs will have to take care of a larger number of patients because of demographic changes and an aging population, and catchment areas will increase [ 4 ]. Furthermore, GPs—especially in rural areas—have problems finding successors for their practices [ 5 , 6 ]. As a result, imbalances, disparities, and inequitable distributions of care occur, which threaten the comprehensive provision of care and the maintenance of population-wide health [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, the literature has shown that practitioners, as well as patients, have certain reservations when it comes to forming attitudes and use intentions toward digital health care technologies. On the professional side, empirical results indicate that some GPs think that a large portion of their patients, especially older patients, are not able to operate digital technologies, which hinders the effectiveness and progress of treatments [ 77 ]. On the patient side, low technology adoption rates can occur, inter alia, because of the desire to maintain a personal and direct relationship to their GP or the lack of familiarity with the respective technologies [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…or "Under which circumstances would you likely accept such a telemedicine system?". In our process of primary analysis, we noticed that physicians basically tend to reject a specific telemedicine system when they had the impression that the telemedicine system limited their own sensory perception of the patient (Mueller et al 2020). To follow up on our impression that a limited perception through digital technology might lead to a physician's rejection of telemedicine systems, we evaluated the key concept of limiting factors concerning telemedicine system use separately.…”
Section: Methodsmentioning
confidence: 99%
“…In our primary study to explore factors influencing a digitally enhanced relationship between patient and therapist (Mueller et al 2020) we conducted seven semistructured interviews with primary care physicians in rural areas to explore their perception on healthcare digitization, especially on potentials of telemedicine systems. Therefore, our major focus of the interviews was physicians' technology acceptance of such telemedicine systems.…”
Section: Methodsmentioning
confidence: 99%